2008
DOI: 10.1002/cjce.5450840110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Hydrodynamics and Regime Transition in Bubble Columns

Abstract: The detailed flow structures in bubble columns with and without internal draught tube have been investigated using the PIV technique. The onsets of transition due to vortex formation and different flow patterns with and without draught tube have been studied using the drift‐flux model and the experimentally measured Reynolds stresses. The role of solid particles and liquid viscosity, as well as bubbling orifice configuration on the flow patterns and regime transition has also been studied and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
2
0
3
Order By: Relevance
“…It means that under the uniform liquid flowing condition there also exists a macroscale liquid circulation loop in the column. Such an observation is just on the contrary to the results reported in a number of studies but is consistent with the findings of Hills and other workers. , This may be due low gas flow rates; although the flow is uniform, the rising gas bubbles may move upward not in a straight line but in a spiral manner or in a meandering way, , which will also carry liquid upward in their wakes, thus inducing the convective circulation flow of liquid. It should be noted that the motion of liquid circulation flow under this condition is not vigorous and the liquid circulation velocity is much slower compared with that under the churn turbulent flow regime.…”
Section: Resultssupporting
confidence: 91%
“…It means that under the uniform liquid flowing condition there also exists a macroscale liquid circulation loop in the column. Such an observation is just on the contrary to the results reported in a number of studies but is consistent with the findings of Hills and other workers. , This may be due low gas flow rates; although the flow is uniform, the rising gas bubbles may move upward not in a straight line but in a spiral manner or in a meandering way, , which will also carry liquid upward in their wakes, thus inducing the convective circulation flow of liquid. It should be noted that the motion of liquid circulation flow under this condition is not vigorous and the liquid circulation velocity is much slower compared with that under the churn turbulent flow regime.…”
Section: Resultssupporting
confidence: 91%
“…Zahradník et al (1997) studied the duality of the flow regimes in bubble columns. Thet et al (2006) performed good experimental studies on hydrodynamics and regime transitions in bubble columns. An interesting method for flow regime identification in high-pressure bubble columns has been presented by Lin et al (1999) All researchers reported that the mode of primary gas dispersion (bubbling regime) may essentially influence the character of the gas-liquid bubble beds and the respective values of its hydrodynamic and mass transfer characteristics.…”
Section: Description Of Main Flow Regimes In Bubble Columnsmentioning
confidence: 98%
“…Thet et al [ 65 ] investigated hydrodynamics and regime transition in bubble columns. In the study, experiments are carried out with and without an internal draught tube.…”
Section: Introductionmentioning
confidence: 99%